Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

I'm attempting to evaluate the limit


I got it reduced to the following


But putting in $\infty$ I get $\frac{1}{0}$ and, what's worse, Mathematica tells me the limit is equal to $-\infty$. Where am I going wrong?

share|cite|improve this question
I have amended my solution. I think that solves your doubt. – Easy May 7 '13 at 16:03
This problem looks a little bit unclear to me, if I interpret $x \rightarrow \infty$ as $x \rightarrow + \infty$, I'll have some way to solve it, but if I interpret it as $x \rightarrow - \infty$, then I'll have a completely different way to solve. – user49685 May 7 '13 at 18:08
up vote 4 down vote accepted

\begin{align*} &\lim_{x\rightarrow\infty}\frac{1}{\sqrt{x^{2}-4x+1}-x+2}\\ =&\lim_{x\rightarrow\infty}\frac{1}{\sqrt{(x-2)^2-3}-(x-2)}\\ =&\lim_{x-2\rightarrow\infty}\frac{1}{\sqrt{(x-2)^2-3}-(x-2)}\\ =&\lim_{z\rightarrow\infty}\frac{1}{\sqrt{z^2-3}-z}\\ =&\lim_{z\rightarrow\infty}\frac{\frac{1}{z}}{\sqrt{1-\frac{3}{z^2}}-1} \end{align*} Note that the absolute value of the last expression is $\infty$ and the denominator is negative as $\sqrt{1-\frac{3}{z^2}}<1$.

share|cite|improve this answer

Hint: multiply top and bottom by $\sqrt{x^2-4x+1}+x-2$.

Additional hint upon request: $\lim_{x\rightarrow \infty}\sqrt{x^2-4x+1}=\infty$ and $\lim_{x\rightarrow \infty} x-2=\infty$.

share|cite|improve this answer
You were first :) – Mårten W May 7 '13 at 13:58
@MårtenW, my typing may be fast, but I make a lot of mistakes. – vadim123 May 7 '13 at 13:59
Okay, so I end up with $\lim_{x\rightarrow\infty}\frac{\sqrt{x^{2}-4x+1}+\left(x-2\right)}{-3}$ – Dmitri Nesteruk May 7 '13 at 14:22



Let us put $x-2=\sqrt3\csc2\theta$

$x\to\infty\implies \theta\to0$

So, $$F=\lim_{\theta\to0}\frac1{\sqrt3\cot2\theta-(\sqrt3\csc2\theta+2)+2}$$


$$=-\frac1{\sqrt3}\lim_{\theta\to0}\frac{2\sin\theta\cos\theta}{2\sin^2\theta}$$ (using $\sin2\theta=2\sin\theta\cos\theta,\cos2\theta=1-2\sin^2\theta$)

$$=-\frac1{\sqrt3}\lim_{\theta\to0}\cot\theta$$ as $\theta\to0\implies \sin\theta\to0\implies \sin\theta\ne0$

What is $\cot0?$

share|cite|improve this answer
This is an epic answer. – Dmitri Nesteruk May 7 '13 at 18:51

Hint: multiply numerator and denominator by the denominator's conjugate:


Added under request :


share|cite|improve this answer
= $\lim_{x\rightarrow\infty}\frac{\sqrt{x^{2}-4x+1}+\left(x-2\right)}{-3}$, and then? – Dmitri Nesteruk May 7 '13 at 14:25
Check if the added stuff in my answer helps you now, @DmitriNesteruk – DonAntonio May 7 '13 at 16:11

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.